Antioxidant activity and physicochemical analysis of passion fruit (Passiflora glandulosa Cav.) pulp native to Cariri region - Abelardo Barbosa Moreira Lima-Neto; Márcia Maria Mendes Marques; Francisca Noélia Pereira Mendes; Ícaro Gusmão Pinto Vieira; Derlange Belizário Diniz; Maria Izabel Florindo Guedes (Acta Scientiarum. Biological Sciences, 2017)
The objective of this study was to determine the proximal composition, the physical and chemical characteristics and the in vitro antioxidant capacity (DPPH, ABTS and FRAP) of the pulp of the wild passion fruit (Passiflora glandulosa Cav.) from Cariri region, Ceara, Brazil. The results showed that the proximal composition and the caloric value of this passion fruit are similar to other species, but with a high ascorbic acid content. The fruit pulp showed low level of antioxidant activity and low level of polyphenolic compounds followed by three methodologies used. Due to high levels of titratable acidity (3.52) and total soluble solids (17.80° Brix), this fruit can be considered as a high value fruit for commerce. However, it is a species of passion fruit with few studies described in the literature, and more research is needed to assess its nutritional and functional potential.